Assessing need for extracorporeal cardiopulmonary resuscitation for out‐of‐hospital cardiac arrest using Power BI for data visualisation. (20th December 2020) - Ramanan, Mahesh; Gill, Denzil; Doan, Tan; Bosley, Emma; Rashford, Stephen; Dennis, Mark; Shekar, Kiran
Abstract: Objective: To estimate the number of patients in refractory out‐of‐hospital cardiac arrest (OHCA) potentially suitable for transport to an extracorporeal cardiopulmonary resuscitation (ECPR)‐capable hospital in Brisbane, Queensland, Australia, based on outcome predictors for ECPR, ambulance geolocation and patient data. Methods: A retrospective cohort study was performed using data from all patients in OHCA attended by Queensland Ambulance Service between 1 January 2014 and 31 December 2018. The number of refractory arrest patients who could potentially be transferred to an ECPR‐capable centre within 45 min of the time of arrest was modelled using theoretical on‐scene treatment times. Results: Of 25 518 ambulance‐attended OHCA in Queensland during the study period, 540 (2%) patients met criteria of refractory arrest for study inclusion. Further age and arrest rhythm criteria for transport to an ECPR‐capable hospital were met in 253 (47%) study patients, an average of 51 patients per year. In 2018, 72 patients met study criteria for transport to an ECPR‐capable centre. Based on theoretical on‐scene treatment times of 12 and 20 min, in 2018 only 14 (19%) and 11 (15%) patients respectively would potentially arrive at an ECPR‐capable hospital within accepted timeframes for ECPR. Conclusions: Retrospective data collected from existing ambulance databases can be used to model patient suitability for ECPR. Relatively few patients with refractory OHCA in Queensland, Australia, could be attended and transported to an ECPR‐capable centre within clinically acceptable timeframes. Further studies of the transport logistics and economic implications of providing ECPR services for OHCA are required to better inform decisions around this intervention. Abstract : Retrospective data collected from existing ambulance databases can be used to model patient suitability for extracorporeal cardiopulmonary resuscitation. Relatively few patients with refractory out of hospital cardiac arrest in Queensland, Australia, could be attended and transported to an extracorporeal cardiopulmonary resuscitation‐capable centre within clinically acceptable timeframes.